2015
DOI: 10.1016/j.homp.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The use of animal models in homeopathic research – a review of 2010–2014 PubMed indexed papers

Abstract: In our updated review of the past 5 years, we found further demonstrations of the biological effects of homeopathy using more refined animal models and in vitro techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 54 publications
1
16
0
3
Order By: Relevance
“…Since the 1970s, a large body of experimental work has been amassed, including work carried out in Russia [1][2][3][4][5][6][7], which shows that high dilutions no longer containing molecules of the original substance are able to cause a physiological reaction based on molecular-level effects. A number of properties commonly attributed to "high dilutions" have been discovered [8].…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1970s, a large body of experimental work has been amassed, including work carried out in Russia [1][2][3][4][5][6][7], which shows that high dilutions no longer containing molecules of the original substance are able to cause a physiological reaction based on molecular-level effects. A number of properties commonly attributed to "high dilutions" have been discovered [8].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of homeopathic medicines in relation to the vehicle (placebo) may be seen in studies performed in-vivo or in standard clinical trials. 8,9,[14][15][16][19][20][21][22][23] However, characterizing the specificity of such effects is even more important in refined studies designed in-vitro, 44 since it is known that the succussion itself can promote changes in the solvent organization, including the generation of different oxygenderived radicals, mainly when water is used. [45][46][47] Macrophage cultures are very sensitive for detecting the effect of high dilutions but are also sensitive for detecting such solvent changes as well, concerning elements related to cell oxidative metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…7 Considering the difficulty associated with establishing an effective therapeutic protocol, the search for alternatives is critical. Several studies have demonstrated specific and relevant effects of homeopathic medicines in animals of different species under various nosological conditions; [8][9][10] nevertheless, the understanding of the general mechanisms through which such agents exert their effects is still very poor. 10 Some previous clinical experience of one of the co-authors of this article was the main motivation for this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the production of animals, homeopathy is studied in experimental models such as rats, mice and non-human primates (Bonamin et al, 2015;Chatfield et al, 2016). In this group, rats and mice correspond to 72% of the research of this therapy in the last 10 years, with the main purpose of using them as models of disease (Chatfield et al, 2016).…”
Section: Introductionmentioning
confidence: 99%